2014
DOI: 10.1111/jpy.12173
|View full text |Cite
|
Sign up to set email alerts
|

Phototrophic pigment production with microalgae: biological constraints and opportunities

Abstract: There is increasing interest in naturally produced colorants, and microalgae represent a bio-technologically interesting source due to their wide range of colored pigments, including chlorophylls (green), carotenoids (red, orange and yellow), and phycobiliproteins (red and blue). However, the concentration of these pigments, under optimal growth conditions, is often too low to make microalgal-based pigment production economically feasible. In some Chlorophyta (green algae), specific process conditions such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(146 citation statements)
references
References 95 publications
3
137
0
6
Order By: Relevance
“…In addition, these microalgae are well known for the synthesis of fucoxanthin and important antioxidant carotenoid. Fucoxanthin is mainly naturally found in marine microalgae, associated with thylakoid membranes, and it works by transferring excitation energy to chlorophyll a, driving electrons to the electrons transport chain [28,29]. Fucoxanthin is usually found to be 0.22-1.82% in the biomass of these microalgae, but it can reach much higher concentrations in Isochrysis cultured at proper light intensity, cell density, and mixing.…”
Section: Light Intensitymentioning
confidence: 99%
“…In addition, these microalgae are well known for the synthesis of fucoxanthin and important antioxidant carotenoid. Fucoxanthin is mainly naturally found in marine microalgae, associated with thylakoid membranes, and it works by transferring excitation energy to chlorophyll a, driving electrons to the electrons transport chain [28,29]. Fucoxanthin is usually found to be 0.22-1.82% in the biomass of these microalgae, but it can reach much higher concentrations in Isochrysis cultured at proper light intensity, cell density, and mixing.…”
Section: Light Intensitymentioning
confidence: 99%
“…Fucoxanthin is naturally found in marine organisms, like brown algae (Miyashita et al 2011) and microalgae, where it is coupled to the thylakoid membrane to transfer excitation energy to the photosynthetic electron transport chain via chlorophyll a (Jin et al 2003;Mulders et al 2014). Fucoxanthin concentration ranges from 2.24 to 18.23 mg Fucoxanthin g Dry Weight -1 in microalgae, which is one to three orders of magnitude greater than that found in macroalgae (Xia et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Mulders, K. J., et al [16] identified the structure of chlorophyll as "a hydrocarbon tail connected to chlorin, an aromatic ring that contains a tetrapyrrole in which the central magnesium ion is bound to four pyrrole rings". Chlorophyll is photoreceptor of photosynthesis and has antioxidant and antimutagen characteristics.…”
Section: Increasing the Protein Amount Of Chlorella Vulgaris [Chlorphmentioning
confidence: 99%